Focal Nodulary Hyperplasia of the Liver Due to Congenital Portosystemic Shunt: A Rare Condition Mimicking Hepatocellulary Carcinoma. Issue 1 (January 2017) - Yazal Erdem, Arzu; Emir, Suna; Demir, Haci A.; Özyörük, Derya; Çetin, İlker; Turan, Aynur; Karakuş, Esra
Abstract : Congenital portosystemic shunts are rare vascular malformations that lead to several complications including liver tumors, pulmonary hypertension, and metabolic encephalopathy. We describe a rare case of a 17-year-old girl with an extrahepatic portosystemic shunt presenting recurrent syncope episodes and a liver mass mimicking hepatocellulary carcinoma.